Modeling and simulation of a stand-alone wind turbine supplying an inductive load through a long cable - Zakaria Al-Omari; Walid Emar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper considers the principles of modeling, control, and simulation of variable speed wind turbines (VSWTs), based on a stand-alone doubly fed induction generator (DFIG). The DFIG is used to feed a three-phase highly inductive load through a long cable via a three-phase multi-level frequency converter (MLFC). The proposed MLFC increases the number of voltage levels with less power electronic components as compared to the conventional back-to-back AC/DC/AC converter. The length of the cable (transmission line TL) influences a mismatch between the load and TL impedances; therefore, a reflected signal will occur. If the "incident signal" is a "continuous AC waveform", these waveforms will mix with another oncoming "incident waveform", creating stationery waveforms called "standing waves". The simulation process shows that the value of the transient’s over-voltage that appears either on the windings of the DFIG or across the load reaches twice the DC-link voltage periodically, which may cause premature failure of the DFIG windings and cable insulations. Usually, this is produced by generating high harmonics within the loads. Therefore, the main benefit of using the MLFC is the significant reduction of the total harmonic distortion and enhancement of the load voltage waveforms. This was verified, primarily by using the "MATLAB/Simulink, Simplorer 7" simulation software.